Customer Relationship Management (CRM) PT Bhineka Rahsa Nusantara dalam Perspektif Kepuasan Pelanggan - Anggun Dewayani; Sri Widayanti; Nisa Hafi Idhoh Fitriana (Universitas Batanghari Jambi, 2023)
Customer relationship management is a tool for companies to be able to get, and create good relationships with customers so that they can be a source of profit for the sustainability of business processes. PT Bhinkea Rahsa Nusantara makes customer relationship management as one of the strategies in order to produce satisfaction for customers, so this study aims to determine the factors of customer relationship management that affect customer satisfaction. This research uses a factor analysis method with SMART-PLS software, with the results of research variables that affect customer satisfaction are identification, interaction, and problem solving together.